ISO 9001:2015 EDITION- MANAGEMENT, QUALITY AND VALUE - Fonseca, Luís (2017)
The aim of this research is to evaluate, six months after the issuing of ISO 9001:2015, if the 2015 edition has achieved its aims of being in line with modern management and quality management concepts and bring additional value to organizations of all industry and services sectors worldwide. A survey was carried out among IRCA registered auditors and the statistical analysis of the results support the assumption that ISO 9001:2015 is in line with modern business and quality management concepts and will be a useful tool for the companies. Although the authors acknowledge pursuing further in-depth studies, this is a relevant contribution to the validation of ISO 9001:2015 edition and its value for all type of organizations worldwide.